(untitled) (Research, Society and Development, 2026)
Objective: To evaluate the perception and level of knowledge of Gynecology and Obstetrics resident physicians regarding vaginismus at a referral hospital in the state of Pará, Brazil. Methods: This was an observational, cross-sectional, and descriptive study conducted with 54 Gynecology and Obstetrics residents at the Fundação Santa Casa de Misericórdia do Pará in 2025. Data were collected through a structured questionnaire developed by the researchers, which included sociodemographic variables and questions addressing the diagnosis, pathophysiology, management, and perception of vaginismus. Data were collected electronically and analyzed descriptively. Results: A high level of recognition of basic concepts related to vaginismus was observed, such as its non-restriction to deep pain or exclusively to sexual intercourse. However, 59.3% of the residents incorrectly classified vaginismus as a psychiatric condition. A significant deficit in practical training was identified, with only 5.6% reporting exposure to pelvic floor physiotherapy during residency and 81.5% expressing insecurity in guiding pelvic floor exercises. Furthermore, 100% of participants considered the support provided by the Brazilian Unified Health System insufficient for the management of vaginismus and acknowledged structural limitations in access to multiprofessional treatment. Conclusion: Despite satisfactory theoretical knowledge of general aspects, relevant gaps persist in conceptual understanding, practical training, and multiprofessional management of vaginismus. These findings highlight the need to strengthen education in female sexual health during medical residency, with the aim of reducing underdiagnosis and improving the quality of care provided to women with vaginismus.